Actual and perceived motor competence in children from Chilean Patagonia: perception of the students and their physical education teachers Competencia motriz real y percibida en niños y niñas de la Patagonia Chilena: La percepción del estudiantado y del profesorado de Educación Física - Gonzalez-Huenulef, Yinali; Martino-Fuentealba, Pía; Bretz, Kathrin; Ferbol Ramirez, Cristina Elizabeth; Carcamo-Oyarzun, Jaime (My University, 2023)
The promotion of motor competence during childhood is one of the main objectives of physical education (PE) class according to UNESCO. For its development, it is important for students to perceive themselves as competent, and for teachers to perceive how competent their students are in the motor tasks they offer in their classes. This study aims at analyzing the relationship between students' and PE teachers' perception of actual motor competence. A total of 248 students (46% girls; age M=11.2; SD=0.94) of 5th and 6th year of primary school from schools in Chilean Patagonia participated in the study. We assessed actual and perceived motor competence with the MOBAK 5-6 test and the SEMOK questionnaire, respectively. We used Pearson's coefficient to determine the relationships; Student's t-test to determine differences according to sex; and calculated a difference component (delta) to determine the difference between actual and perceived motor competence of both students and teachers. We found moderate and weak-moderate relationships between the actual motor competence and the students' perception (Object Control r=0.401; Self-movement r=0.402), and their physical education teachers' perception (Object Control r=0.352; Self-movement r=0.264). The teachers (Δ=1.94) present a more accurate perception than the students (Δ=2.46) only in motor competence related to object control. The perception of competence allows a closer look at the actual motor competence. Physical education teachers can predict the motor performance of their students and could use this information as a resource for the preparation of activities that aim at the development of the students' motor competence.
Keywords: competence; motor development; motor skills; perception